Perlekatan koloni Streptococcus mutans pada permukaan resin komposit sinar tampak (The adherence of Streptococcus mutans colony to surface visible light composite resins) - Ajeng Anggraeni; Anita Yuliati; Intan Nirwana (Dental Journal (Majalah Kedokteran Gigi), 2005)
Visible light composite resins was used to restore anterior and posterior teeth, and it is always covered by saliva pellicle. S. mutans can adhere to all of the surface of oral cavity and visible light composite resins. The aim of this study was to know the amount of S. mutans colony adherence to visible light composite resins surface. The sample of 5 mm diameter and 3 mm in thickness was immersed in saliva for one hour, than the samples were put into bacteria suspension, incubated for 24 hours at 37° C. The amount of S. mutans was determined by direct count using microscope. The data were statistically analyzed by using t test. The result showed a significance difference of S. mutans colony between hybrid and micro fill visible light composite resins. The conclusion was that the amount of S. mutans adherence on the surface of hybrid was higher than the micro fill visible light composite resins.